Use of Al2O3-SnO2 as a support of Pt for selective dehydrogenation of light paraffins - Ballarini, Adriana Daniela (2008)
The influence of the preparation methods of Al2O3-SnO2 on the catalytic behaviour of Pt supported on the above supports in the n-butane dehydrogenation reaction was studied. Two methods were used for the preparation of the support with different Sn loadings: (i) incipient impregnation and (ii) impregnation with an excess of solution. It was determined that the second preparation method would lead to more homogeneous catalysts than the incipient impregnation with SnCl2. Different characterization techniques (XPS, TPR, SEM, test reactions of the acidic and metallic functions, H2 chemisorption) showed that geometric effects and also possible electronic effects between Pt and Sn with probable alloys formation could take place in Pt/Al2O3-SnO2 catalysts. In all cases it was found an excellent behaviour in the n-butane dehydrogenation even when higher Sn contents in the support were used.